Servicio web basado en analítica de datos en la nube para instituciones de educación superior - Brito Casanova , Geovanny José (2025)
This project develops a cloud-based web service for data analytics, aimed at interpreting academic information from digital systems. Currently, data analytics tools often operate in isolation, making it difficult to integrate key data and hindering evidence-based pedagogical and administrative decision-making. The work began by defining a structure to consolidate scattered educational data, process it using machine learning techniques, and return information in a way that facilitates interpretation. Subsequently, a large-scale pre-trained language model was integrated to generate interpretations of the analyses in terms understandable to end users (teachers and academic managers), promoting informed decision-making. The service development included stages of design, implementation, and validation, focusing on ensuring applicability across different educational contexts. The results include a data format that enables interoperability, along with the data processing mechanism. In addition, a web application was developed to showcase the service's functionality and enable practical evaluation through a case study. Thus, this project aims to provide a solution that integrates educational data analysis in higher education institutions, allowing developers to consolidate information and automate interpretation processes to support pedagogical decision-making.